The Discovery of the Titanic - Ballard, Robert D.; Archbold, Rick, 1950- (New York, N.Y. : Warner Books, 1995)
Here is the first-hand account of Dr. Ballard's quest to find the Titanic. Including rare archival photos and charts, this volume recounts the Titanic's tragic last night and describes the drama of the expedition that finally found and explored her. Plus Dr. Ballard reveals the ship's location and lays to rest many of its mysteries. 48-page color insert.
Search for a legend -- What happened that night -- Quest begins -- Watching from the sidelines -- Jason and the Argonauts -- Discovery -- Titanic found -- Touring the Titanic -- last resting place -- Titanic reconsidered -- Epilogue -- Photograph & illustration credits -- Index.
"A Warner/Madison Press book."
Includes index.
Keywords: Titanic (Steamship); Titanic (Steamship); Shipwrecks -- North Atlantic Ocean; Underwater exploration -- North Atlantic Ocean; Naufrages -- Atlantique Nord; Exploration sous-marine -- Atlantique Nord; Shipwrecks; Underwater exploration; North Atlantic Ocean